2020
DOI: 10.1002/jccs.202000125
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis of novel benzimidazoles with a naphthalene moiety as antimicrobial agents and molecular docking studies

Abstract: In an attempt to design a greener approach for the synthesis of a potent class of antimicrobials, 1,2‐phenylenediamine derivatives were reacted with various 1/2‐carboxylic acid‐substituted naphthalene derivatives to generate a series of naphthyl‐substituted benzimidazole derivatives (11–19) using polyphosphoric acid as catalyst under microwave irradiation and conventional synthesis method. This is an eco‐friendly and swift reaction method for a synthetic approach to diverse benzimidazoles. Structures of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The derivatives are effective against drug-resistant Mtb and some possess a bactericidal approach. The synthesis of naphthyl-substituted benzimidazole derivatives ( 88) and ( 89) was reported by Ersan et al in 2020 [77]. The antimicrobial activity was screened and was found that (89) showed maximum potency against all gram-positive and gram-negative bacteria.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…The derivatives are effective against drug-resistant Mtb and some possess a bactericidal approach. The synthesis of naphthyl-substituted benzimidazole derivatives ( 88) and ( 89) was reported by Ersan et al in 2020 [77]. The antimicrobial activity was screened and was found that (89) showed maximum potency against all gram-positive and gram-negative bacteria.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…Among the nitrogen-containing compounds, benzazoles (benzimidazole, benzoxazole, and benzothiazole, etc.) are a subject of great interest to our research group for investigating drug development due to their known pharmacological and biological activities [2][3][4][5][6][7][8][9][10][11]. Benzimidazole is primarily de ned as a privileged substructure in terms of purine-like scaffold feature and its ability to interact with various unrelated molecular targets [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is very volatile and burns with a smoky flame [1]. There are some drugs containing naphthalene, such as nafcillin, naftifine, tolnaftate, and terbinafine [2], which play a crucial role in the management of microbial infections. Naphthalene mono hydroxide derivatives are called naphthol [3,4].…”
Section: Introductionmentioning
confidence: 99%